Association between the triglyceride-glucose index and its combined obesity indicators and the risk of hypertension in middle-aged and older Chinese adults: A nationwide cross-sectional study - Huoping Zheng; Meiling Xu; Jing Yang; Mingjun Xu (PLoS ONE, 2025)
Objective This study aimed to explore the association between the triglyceride-Glucose Index (TyG) and its combination with obesity indicators in relation to the risk of hypertension among middle-aged and elderly individuals in China. Methods A total of 9,248 participants aged 45 and above were selected from the 2015 China Health and Retirement Longitudinal Study. Data on basic demographics, behavioral habits, medical history, physical examination results, and blood indicators were collected. The TyG and its obesity-related indicators, including TyG-BMI, TyG-WC, and TyG-WHtR were analyzed. These indicators were categorized into four groups based on quartiles, and the prevalence of hypertension within each group was assessed. Logistic regression analysis was conducted to evaluate the association between different TyG indices and obesity-related indicators with the risk of hypertension. Additionally, a restricted cubic spline model was employed to investigate the dose-response relationship between the TyG index, its combined obesity indicators, and the risk of hypertension. The receiver operating characteristic curve was utilized to determine the optimal predictive index for diagnosis. Results This study included a total of 9,248 middle-aged and elderly individuals aged 45 and above, comprising 4,274 males (46.21%), with an average age of 61.38 ± 9.28 years. The prevalence of hypertension exhibited an increasing trend as the quartiles of TyG, TyG-BMI, TyG-WC, and TyG-WHtR rose. After fully adjusting for covariates, comparisons between the first quartile (Q1) and the fourth quartile (Q4) of TyG, TyG-BMI, TyG-WC, and TyG-WHtR revealed that all these metrics at Q4 level were associated with an increased prevalence of hypertension. The odds ratios were as follows: TyG: OR = 1.80 (95% CI: 1.48–2.19); TyG-BMI: OR = 5.09 (95% CI: 4.33–5.98); TyG-WC: OR = 3.96 (95% CI: 3.38–4.65); TyG-WHtR: OR = 3.91 (95% CI: 3.33–4.60). A linear correlation was observed between TyG and the risk of hypertension (P for non-linearity = 0.2267), while non-linear correlations were noted between TyG-BMI, TyG-WC, and TyG-WHtR with the risk of hypertension (P for non-linearity < 0.001). The receiver operating characteristic curve indicated that TyG-WC demonstrated the highest diagnostic performance for hypertension, with an area under the curve of 0.642 (95% CI: 0.631–0.654). Conclusion As the levels of TyG, TyG-BMI, TyG-WC, and TyG-WHtR increased, the risk of hypertension among middle-aged and elderly individuals aged 45 and above in my country rises significantly. Among them, TyG-WC can be a predictor of hypertension in middle-aged and elderly people.